The Role Of Free Cash Flow, Bankruptcy Prediction and The Audit Committee In Earnings Management - Sinaga, Reni Haryati; Rahma , Ayumi (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The research aims to analyze and obtain evidence regarding the influence of free cash flow, bankruptcy prediction and audit committees on earnings management. The type of research used is descriptive quantitative. The population of this study is the Financial Sector Industry which is listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample selection technique uses the methodpurposive sampling. The amount of data obtained was 39 companies from 156 data. The data analysis method used is descriptive statistics, panel data regression test, classical assumption test, and multiple linear regression, t statistical test and F statistical test using the Microsoft Office Excel Program and Eviews 12 Statistics Program. The results of this study indicate that Free Cash Flow has an effect significant to Earnings Management, while Bankruptcy Prediction and Audit Committee have no effect on Earnings Management. Meanwhile, Free Cash Flow, Bankruptcy Prediction, and Audit Committee jointly (simultaneously) affect Earnings Management.